The Application of Scaffolding Technique: Think-Pair-Share (TPS) to Improve the English Speaking Skills of Grade XI Students at SMA Negeri 1 Penebel in the 2024/2025 Academic Year - Dewi, Ni Luh Made Winda Sri (English Education and Literature Journal (E-Jou), 2026)
This study aims to improve the english speaking skill of Grade XI-1 students at SMA Negeri 1 Penebel n the 2024/2025 academic year through the application of the Scaffolding Technique using the Think Pair and Share (TPS) strategy. Speaking is one of the essential language skill that reflect students’ communicative competence; however, many students continue to face challenges in vocabulary use, grammatical accuracy, pronunciation, and confidence. To address these issues, this research employed a Classroom Action Research design, which was conducted following the model proposed by Kemmis and McTaggart. The study focused on how the TPS strategy, as a form of scaffolding, could actively engage students in speaking and gradually enhance their performance. The study was implemented in two cycles, each consisting of planning, action, observation, and reflection. The results showed progressive improvement across the cycles. The pre-test score totaled 370 with an average of 12.76 and 63.79% of students achieving the minimum mastery criterion (KKM). After Cycle I, the total score increased to 392 with an average of 13.52 and a completeness rate of 67.59%. Significant improvement was recorded in Cycle II, where the total score reached 483, the average rose to 16.66, and completeness reached 83.28%. These findings indicate that the TPS technique effectively enhanced students’ speaking skills by fostering collaborative learning, active participation, and structured oral practice. It also increased student engagement and confidence in speaking English. The study recommends the use of TPS as an alternative strategy to improve speaking performance in EFL classrooms